Spazi urbani sicuri strategie e azioni per un approccio integrato alla qualità insediativa - Coppola, Francesca (TRIA Urban Studies, 2021)
One of the main requirements for well-functioning cities, and for their sustainability is that they have secure streets and public spaces. This circumstance is reaffirmed by the Sustainable Development Goals (SDG), in particular SDG 11 by which the creation of secure, as well as inclusive, resilient and sustainable cities is promoted. Security in the city is hindered everyday by the occurrence of predatory crimes or incivility episodes that affect the perception of insecurity raising fear. The growing demand for security that citizens ask for requires a new perspective with respect to the approaches that have been adopted so far to deal with this problem. The objective of making the city safer cannot be pursued exclusively through control or repressive actions or with occasional and generalised social interventions. It is necessary to address the issue in a multidisciplinary and multi-level perspective, following an integrated approach that incorporates considerations, abilities, strategies and actions of an urban planning, architectural, social, criminological, legal and political nature. This collection is an opportunity to reflect, in a more careful way, on a particularly complex issue, integrating different knowledge and points of view that can guide Urban Planning towards the preparation of specific actions, possibly to be included in the Municipal Urban Plan, for the adaptation, over time, of urban spaces to security criteria.